(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article analyzes the key factors for enhancing educational effectiveness in the modern learning environment. The research focuses on the interconnection between student motivation, the implementation of interactive methodologies, and objective assessment systems. The paper argues that supporting learners’ intrinsic motivation and organizing lessons through modern ICT tools fundamentally improve the quality of education. Furthermore, the function of assessment is examined in detail, emphasizing its role not only as a control mechanism but also as a developmental tool.